Tafsir Ayat-Ayat Al-Qur'an Tentang Kewajiban Belajar Mengajar - Aidil Fitrah; Bella Amanilla; Rafidi Rafidi; Agus Rifki Ridwan (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Learning and teaching from the perspective of the Qur'an are not only understood as intellectual activities, but also as spiritual, emotional, and moral processes that shape the whole human personality. Learning is an obligation for every individual to develop their human potential and get closer to Allah SWT, while teaching is seen as worship and a social responsibility in spreading knowledge and good values. This study aims to examine the interpretation of the verses of the Qur'an related to the obligation of learning and teaching, namely QS. At-Taubah: 122, QS. Al-Ghasiyah: 17–20, QS. Al-'Ankabut: 19–20, QS. Al-Qalam: 1–4, and QS. Al-'Alaq: 1–5. The method used is a literature study with a thematic interpretation approach (maudhu'i). The results of the study indicate that the obligation of learning and teaching is lifelong (long life education) and is an important foundation in building an Islamic civilization that is moral, knowledgeable, and competitive.